2014
DOI: 10.1128/jb.01897-14
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Secretion of Noncatalytic Plant Cell Wall-Binding Proteins by the Cellulolytic Thermophile Caldicellulosiruptor bescii

Abstract: Caldicellulosiruptor bescii efficiently degrades cellulose, xylan, and native grasses at high temperatures above 70°C under anaerobic conditions. C. bescii extracellularly secretes multidomain glycoside hydrolases along with proteins of unknown function. In this study, we analyzed the C. bescii proteins that bind to the cell walls of timothy grass by using mass spectrometry, and we identified four noncatalytic plant cell wall-binding proteins (PWBPs) with high pI values (9.2 to 9.6). A search of a conserved do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…In addition to CBMs within modular enzymes, Caldicellulosiruptor species also use noncatalytic proteins to bind to lignocellulosic substrates. Transcriptomic and proteomic analysis of cellulose-bound Caldicellulosiruptor cultures identified the presence of carbohydrate binding proteins (19), including the recently characterized 'tāpirins' (20). Tāpirins typically have a Mr of 105 approximately 70 kDa as a single polypeptide; recombinant versions from C. kronotskyensis have a specific affinity for cellulose fibers in plant material and an affinity for Avicel similar to that of CBM3s, despite no significant structural homology (20).…”
Section: Introduction 70mentioning
confidence: 99%
“…In addition to CBMs within modular enzymes, Caldicellulosiruptor species also use noncatalytic proteins to bind to lignocellulosic substrates. Transcriptomic and proteomic analysis of cellulose-bound Caldicellulosiruptor cultures identified the presence of carbohydrate binding proteins (19), including the recently characterized 'tāpirins' (20). Tāpirins typically have a Mr of 105 approximately 70 kDa as a single polypeptide; recombinant versions from C. kronotskyensis have a specific affinity for cellulose fibers in plant material and an affinity for Avicel similar to that of CBM3s, despite no significant structural homology (20).…”
Section: Introduction 70mentioning
confidence: 99%
“…In addition to CBMs within modular enzymes, Caldicellulosiruptor species also use noncatalytic proteins to bind to lignocellulosic substrates. Transcriptomic and proteomic analysis of cellulose-bound Caldicellulosiruptor cultures identified the presence of carbohydrate binding proteins (20), including the recently characterized "ta pirins" (21). Ta pirins typically have a M r of approximately 70 kDa as a single polypeptide; recombinant versions from C. kronotskyensis have a specific affinity for cellulose fibers in plant material and an affinity for Avicel similar to that of CBM3s, despite the absence of significant structural homology (21).…”
mentioning
confidence: 99%
“…Some of the modular enzymes from the genus Caldicellulosiruptor are cell-anchored using S-layer homology domains (30) and are hypothesized to mediate cell-substrate proximity. In addition, substrate-binding proteins (in some cases, components of ATP-binding cassette transporters (24,31)) may also play a role in orienting Caldicellulosiruptor species toward carbohydrate moieties in plant biomass, possibly through positively charged amino acid residues interacting with negatively charged areas (32). However, comparative proteogenomics analysis of whole cell, extracellular, and cellulose-bound fractions of Caldicellulosiruptor species revealed that previously annotated hypothetical proteins (referred to here as "ta pirins" taken from the Ma ori verb "to join") bound tightly to cellulose, thereby implicating yet another element in the mechanism by which these bacteria attach to plant biomass.…”
mentioning
confidence: 99%